A Sub-Threshold Microwave RFID Tag Chip, Compatible With RFID MIMO Reader Technology - Haddadian, Sanaz; Scheytt, J. Christoph; von Bögel, Gerd; Grenter, Thorben (IEEE Journal of Radio Frequency Identification)
We present a fully integrated radio frequency identifications transponder chip operating at 5.8 GHz, which is compatible with the class-1 generation-2 of the Electronic Product Code protocol (EPC-C1 G2). The tag chip including the analog front-end and the digital baseband processor, are designed in the sub-threshold regime (0.5 V) with a total supply current of less than 50 μA. As a power scavenging unit, a single-stage differential-drive rectifier structure is designed and fabricated with standard threshold voltage (SVT) MOS elements in a commercial 65-nm CMOS process, to provide 0.8 V of rectified voltage. Measurements performed on the fabricated single-stage structure show a maximum power conversion efficiency of 69.6% for a 22 kΩ load and a sensitivity of -12.5 dBm, which corresponds to more than 1 m of reading range. The power conversion efficiency at this range is about 64%.